Sensory and Microbiological Properties of Pickled Bamboo Shoots (Bambusa vulgaris) - Mokhammad Khoiron Ferdiansyah; Ulfa Setiwati; Enny Purwati Nurlaeli; Fafa Nurdyansyah (Engineering Faculty, University of Pembangunan Nasional Jawa Timur, 2020)
Most people currently preserve bamboo shoots (Bambusa vulgaris) that have been harvested using alum which has an adverse effect on the human body. Alternative preservation of bamboo shoots can be done by making bamboo shoots using a solution of sugar and salt solution. This study aims to determine the effect of salt and sugar concentrations on the sensory and microbiological properties of pickled bamboo shoots. The design used was the factorial method in the basis of a completely randomized designs (CRD) using two factors, namely salt solution and sugar solution. The formulation used were sugar concentration 1%; 2%; 3% and salt concentration 10%; 12.5%; 15% Sensory test results showed that the concentration of sugar and salt affected the hedonic test values of color, aroma, and texture. Whereas microbiological analysis showed that there is an increase in the total plate count by increasing fermentation time